Policy influence in the knowledge space: A regional application - Stefano Basilico; Uwe Cantner; Holger Graf (Friedrich Schiller University Jena, 2021)
Cluster policies aim at improving collaboration between co-located actors to address systemic failures. As yet, cluster policy evaluations are mainly concerned with effects on firm performance. Some recent studies move to the system level by assessing how the structure of actor-based knowledge networks is affected by such policies. We continue in that direction and analyze how technology-based regional knowledge spaces structurally respond to the introduction of a cluster policy. Taking the example of the German BioRegio contest, we examine how such knowledge spaces in winning and non-winning regions evolved before, during and after the policy. Using a difference-in-differences approach, we identify treatment effects of increased knowledge space embeddedness of biotechnology only in the post-treatment period. Our findings imply that cluster policies can have long-term structural effects typically not accounted for in policy evaluations.
Keywords: O31; O38; R11; 330; BioRegio contest; network analysis; knowledge space; difference in differences; patents